Resiliensi Petani dalam Menjaga Produksi Pertanian: Studi di Kecamatan Solokuro, Lamongan - Iva Yulianti Umdatul Izzah; Husainatul Jazilah (Society, 2022)
This research examines how the lives of farmers in rural Lamongan during the pandemic, the challenges faced by farmers during the pandemic, and the forms of resilience that farmers take in maintaining their agricultural productivity in the pandemic era. Data was collected using qualitative research methods and a case study approach to show how farmers carried out the form of resilience in rural areas in Lamongan Regency during the COVID-19 pandemic. There were eight informants whose data were extracted in this research consisting of four male farmers and four female farmers. Observations and interviews with informants were carried out from July to October 2020. This research occurred in a rural area, namely in Dadapan Village, Solokuro Subdistrict, Lamongan Regency, East Java, considering that farmers in the village still carry out farming activities even though they are in a pandemic condition. From this research, it can be seen that farmers in Dadapan Village are the affected parties during the pandemic and must make efforts to survive. The challenge farmers face the losses experienced due to difficulties in marketing their agricultural products. Farmers’ resilience forms include, first, continuing to do farming during this pandemic while still paying attention to health protocols; second, creating marketing strategies for their agricultural products online; and third, maintaining their enthusiasm to continue farming.